401 Maternal postpartum depression is associated with increased risk of early childhood injury. (1st September 2016) - Currie, Dustin W; Colangelo, Claire; Quigley, Mallory; Cares, Alexa; O'Fallon, Molly; Thorland, William
Abstract : Background: Previous research indicates an association between maternal postpartum depression (PPD) and child maltreatment, but research on this association in child injury outside of the maltreatment context is limited. The Nurse-Family Partnership (NFP) is a nurse home visiting program in which nurses visit first-time, low-income moms from pregnancy until the child's second birthday, promoting healthy parenting practices. As early childhood injury or ingestion emergency room (ER) visits are primary NFP outcomes, there is an interest in determining risk factors for these outcomes within the client population. Methods: We analysed a cohort of NFP clients beginning the program between 7/1/2010 and 6/30/2012 with completed 12-month infant health care and PPD forms (n = 6271). Postpartum depression was measured using the Edinburgh Postnatal Depression Scale (EPDS) administered 1 to 8 weeks after birth, with a cutoff score of ≥10 indicating possible PPD. The outcome was defined as self-reported infant ER visit due to injury or ingestion on the 6- or 12-month infant health care form. Logistic regression was used to calculate adjusted odds ratios of the relationship between PPD and injury. Results: A total of 985 clients (15.8%) exceeded the possible PPD cutoff on the EPDS. Injury- or ingestion-related ER visits in the child's first year of life were reported by 385 clients (6.2%). Postpartum depression scores above the cutoff were significantly associated with ER visits after adjusting for child gender and maternal race, age, education and marital status (adjusted OR: 1.41 [1.07, 1.84], p = 0.01). Conclusions: We found a significant association between PPD and subsequent risk of childhood injury/ingestion ER visit within a cohort of NFP clients after adjusting for related confounders. Understanding how postpartum depression affects early childhood outcomes may provide opportunities for targeted injury prevention interventions within the home visitation program context.